The effect of light, iron and manganese supply on phytoplankton community composition in the Weddell Sea - Jenna Balaguer; Florian Koch; Scarlett Trimborn (PANGAEA, 2024)
This study highlights the importance of manganese (Mn) next to iron (Fe) for the growth of specific Southern Ocean phytoplankton groups with important implications for primary production in the Weddell Sea. Two Fe-Mn-light bottle amendment experiment were performed with a natural phytoplankton community during Polarstern expedition PS124 in 2021 in the Weddell Sea. At this location, seawater was pumped (using trace metals clean techniques) from 25m depth to fill polycarbonate bottles. The Control treatment consisted of the sampled seawater without any trace metals addition, while the other three treatments were enriched with either FeCl3 alone (0.5 nM; +Fe treatment) or MnCl2 alone (1 nM; +Mn treatment) or both trace metals together (+FeMn treatment). All treatments were done in triplicate 2,5L PC bottles under 2 light regimes (30 and 100 μmol photon m-2 s-1). After on average 7 days, samples for chlorophyll a content, particulate organic carbon, primary production flow cytometry and light microscopy were taken to detect FeMn co-limitation effect on species composition and primary production. While results showed with high confidence that both communities were Fe-limited, no evidence was found that low light provoked a stronger response to Fe supply. Nevertheless, under low light, microscopic analysis at both locations revealed Fe-Mn co-limitation of a key phytoplankton group: Fragilariopsis sp., which numerically dominated the diatom communities. Our findings highlight that in response to light limitation, some key species may suffer from Fe-Mn co-limitation with subsequent implications for the biological carbon pump.